Cost-Effectiveness of Patient Navigation to Increase Adherence with Screening Colonoscopy Among Minority Individuals - Ladabaum, Uri (Cancer, 2014)
BACKGROUND: Colorectal cancer (CRC) screening is underutilized by minority populations. Patient navigation increases adherence with screening colonoscopy. We estimated the cost-effectiveness of navigation for screening colonoscopy from the perspective of a payer seeking to improve population health. METHODS: We informed our validated model of CRC screening with inputs from navigation studies in New York City (population 43% African American, 49% Hispanic, 4% White, 4% Other; base case screening 40% without and 65% with navigation, navigation costs $29/colonoscopy completer, $21/non-completer, $3/non-navigated). We compared: 1) navigation vs. no navigation for one-time screening colonoscopy in unscreened persons age ≥50; 2) programs of colonoscopy with vs. without navigation, vs. fecal occult blood testing (FOBT) or immunochemical testing (FIT) for ages 50-80. RESULTS: In the base case: 1) one-time navigation gained quality-adjusted life-years (QALYs) and decreased costs; 2) longitudinal navigation cost $9,800/QALY gained vs. no navigation, and assuming comparable uptake rates, it cost $118,700/QALY gained vs. FOBT, but was less effective and more costly than FIT. Results were most dependent on screening participation rates and navigation costs: 1) assuming a 5% increase in screening uptake with navigation and navigation cost of $150/completer, one-time navigation cost $26,400/QALY gained; 2) longitudinal navigation with 75% colonoscopy uptake cost <$25,000/QALY gained vs. FIT when FIT uptake was <50%. Probabilistic sensitivity analyses did not alter the conclusions. CONCLUSIONS: Navigation for screening colonoscopy appears to be cost-effective, and one-time navigation may be cost-saving. In emerging healthcare models that reward outcomes, payers should consider covering the costs of navigation for screening colonoscopy.